2018
DOI: 10.1177/2399654418790767
|View full text |Cite
|
Sign up to set email alerts
|

Socio-political drivers and consequences of landslide and flood risk zonation: A case study of Limbe city, Cameroon

Abstract: Disaster risk zonation is often proposed as a long-term disaster risk reduction strategy by international treaties and academic research. This strategy has been implemented in the city of Limbe, which is known to be a disaster-prone one. Citizens are forced to settle in unsafe terrains, ranging from wetlands to unstable hillslopes due to the city’s geographical location and economic attraction. Following the fatal landslides and floods in 2001, a local crisis committee identified affected areas and declared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
(68 reference statements)
0
10
0
3
Order By: Relevance
“…Depending on the Ugandan government, one can expect landslide risk to either be a useful tool to reduce the impact and suffering from disasters, or alternatively to increase inequality between those who have access to safety and stability and those who do not. In other regions, it has been shown that risk zoning maps can lead to the exclusion of people from state support after a landslide because their affected settlements are considered 'illegal' (Maes et al, 2019). Additionally, citizen who can make use of landslide risk maps are generally more likely the most powerful, best informed citizen who can pay for land in non-exposed areas.…”
Section: Risk Is a Tool For Governancementioning
confidence: 99%
“…Depending on the Ugandan government, one can expect landslide risk to either be a useful tool to reduce the impact and suffering from disasters, or alternatively to increase inequality between those who have access to safety and stability and those who do not. In other regions, it has been shown that risk zoning maps can lead to the exclusion of people from state support after a landslide because their affected settlements are considered 'illegal' (Maes et al, 2019). Additionally, citizen who can make use of landslide risk maps are generally more likely the most powerful, best informed citizen who can pay for land in non-exposed areas.…”
Section: Risk Is a Tool For Governancementioning
confidence: 99%
“…Increasing population pressure has led people to settle on the steeper slopes (Guedjeo et al, 2013;Lambi and Ndenecho, 2010), which are frequently affected by both small and large landslides in the raining season (Wouatong et al, 2014;Zangmo et al, 2011), leaving the population exposed. The authorities at both the local and the national level promote a risk zonation policy (Maes et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…However, poor enforcement and the lack of transparency have prevented this policy from leading to effective risk reduction (Maes et al, 2018). Some villages in the Bamboutos caldera have already resettled or have attempted to do so, while others do not consider it a relevant option for now.…”
Section: Study Areamentioning
confidence: 99%
“…In a more global context, researchers have already utilized UPE in disaster studies, such as Marks (2015), analyzing the 2011 flood event in Bangkok, Thailand, and Maes et al (2019) talking about landslide and flood risk zonation. They used UPE to reveal a disaster as an urban socio-ecological issue in a more political context.…”
Section: The Concept Of Urban Political Ecologymentioning
confidence: 99%
“…According to Oliver-Smith (1999, 2004, 2009, vulnerability is a subject of political ecology because it studies human and natural interactions closely related to the political economy. Although some researchers, such as Pelling (1999), Marks (2015), Salami, von Meding, & Giggins (2017), Maes et al (2019) have utilized the urban political ecology (UPE) framework, so far no research has been carried out in the Indonesian context. Notably, there have been no studies that discussed the vulnerability of coastal areas or communities.…”
Section: Introductionmentioning
confidence: 99%